2009
DOI: 10.1351/pac-con-08-08-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular organization and recognition properties of amphiphilic cyclodextrins

Abstract: The continuing challenge of using cyclodextrins (CDs) for solubilization and drug targeting has led to the preparation of a wide variety of chemically modified derivatives in order to improve the properties of these host molecules. A possible approach for pharmaceutical applications would be to combine the recognition specificity of CDs with the transport properties of organized structures such as vesicles, liposomes, or micelles. Amphiphilic CDs can be admixed to phospholipid monolayers and to liposomes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…TCl-1/SCl-1) were measured in the presence of variable levels of PNP using 1-D and 2-D NMR methods in solution to characterize the nature of the copolymer/PNP complexes [37,38]. As noted above, thermodynamic sorption studies provide evidence for the existence of multiple sorption sites for CD-based copolymer sorbents [10,[15][16][17][18][19]. Fig.…”
Section: Spectroscopic Characterization Of the Pnp/copolymer Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…TCl-1/SCl-1) were measured in the presence of variable levels of PNP using 1-D and 2-D NMR methods in solution to characterize the nature of the copolymer/PNP complexes [37,38]. As noted above, thermodynamic sorption studies provide evidence for the existence of multiple sorption sites for CD-based copolymer sorbents [10,[15][16][17][18][19]. Fig.…”
Section: Spectroscopic Characterization Of the Pnp/copolymer Complexesmentioning
confidence: 99%
“…In some cases, isotherm sorption parameters may provide indirect information about the sorption mechanism. Rossi et al [18] reported an amphiphilic CD with multiple recognition sites; whereas, Mohamed et al [11] reported two types of binding sites (i.e. inclusion and interstitial domains) for urethane-based copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in water-solubility was due to the number of carboxylate functions per graft [one for the first series (Table 2; entries 1, 3, 5, 7, 9 and 11) against two for the second series (Table 2; For each compound, the critical aggregation concentration (CAC) and the surface tension (ST) value obtained at this concentration were determined by the Wilhelmy method. [24] Thus, the possibility of a such behavior was checked for -CD- (OSD-Na-[1]-Me)1.6. The dicarboxylate derivatives have a higher CAC than their ester counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the new millennium has witnessed tremendous development in the generation of some novel porphyrin systems by incorporating into them some suitable foreign host material, called molecular receptors. Molecular receptors are macrocyclic, three-dimensional host molecules with guest inclusion capabilities to ensure strong and precise molecular recognition [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Molecular recognition using synthetic compounds is a process where some molecules (hosts) selectively bind other molecules or ions (guests) to produce a well structurally organized system through intermolecular forces and to mimic the mode of action of a natural enzyme by catalyzing specific reactions at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%